The University Workers' Willingness to pay for Commuting - Giovanni Russo; Jos van Ommeren; Piet Rietveld (Tinbergen Institute, 2010)
Using a dynamic approach, employing data on job mobility, we demonstrate that university workers' marginal willingness to pay for reducing commuting distance is about euro 0.25 per kilometre travelled. This corresponds to a marginal willingness to pay for reducing commuting time of about 75% of the net average hourly wage. For females, the willingness to pay is substantially higher than for males. It is also substantially higher for workers that work few hours per day, as predicted by theory.
Keywords: R21; 330; University workers; commuting; Wissenschaftler; Pendelverkehr; Willingness to pay; Amsterdam